Tren Pengembangan Media Pembelajaran Bahasa Arab di Indonesia Era 5.0 - Anisa Alfurochmatin; Ahmad Muhaimin Bin Mat Jusoh (Alsina : Journal of Arabic Studies, 2024)
This study aims to analyze the development methodologies of Arabic language learning media that utilize technology in the 5.0 era, mainly through applications used in the learning process. With the onset of the 5.0 era in 2017, teachers are expected to harness advancing technologies to achieve educational objectives. This study employs the Corpus Approach by collecting 30 articles published over the last five years, between January 2019 and December 2023, using the Google Scholar search engine. The study focuses on identifying development methodologies, product outcomes, types of applications developed, year of publication, article indexing, and the skills (mahārah) intended to be achieved. The results indicate that most developers utilized Research and Development (R&D) methodologies, with 54% employing the ADDIE model, 30% using the Borg & Gall model, 7% using the 4D model, 6% employing the Hannafin Peck model, and 3% using the Lee & Owens model. 80% of the articles developed software applications for PC or Android, while 20% focused on hardware development. The year 2019 saw the highest number of articles submitted. Article indexing includes SINTA 2-5 and conference proceedings. The primary focus of skill development was on vocabulary (mufradāt) mastery and reading (qirā’ah). Feasibility tests showed that 100% of the products were rated as "very feasible and good," supported by validation tests from experts and pre-test and post-test evaluations conducted directly using either T-tests or limited-scale tests.